Effects of nutrient sources and weed management on yield and weed suppression in finger millet (Eleusine coracana L.) - Shraddha, M K; Lalita, R; Navnit, K; Biswajit, P; Sumit, S; Ajeet, K; Jyostnarani, P; Rajan, K; Mukesh , K; Suruchi, K (Plant Science Today, 2026)
Finger millet (Eleusine coracana L.) is a climate-resilient and nutritious crop; however, imbalanced nutrient application and inadequate weed management can limit productivity. A field experiment conducted at Pusa Farm, Dr. Rajendra Prasad Central Agricultural University , Samastipur, Bihar, during kharif 2024. The experiment conducted in a split plot design with two nutrient sources (N1: 100 % Recommended dose of nitrogen (RDN) via chemical fertilizer, N2: 75 % RDN + 25 % RDN via farmyard manure (FYM)) as main plot factor and four weed management practices (W₁: Butachlor at 1.0 kg ha-1 (Pre-emergence (PE)) followed by 2,4-D at 0.5 kg ha-1 (Post-emergence (PoE)); W₂: Oxyfluorfen at 0.1 kg ha-1 (PE) followed by 2,4-D at 0.5 kg ha-1, W3: Weedy check and W4: Weed free as sub-plot factor. Results showed that 100 % RDN increased plant height (101.79 cm), dry matter accumulation (897.8 g m-2) and no. of tillers (5.18 plant-1). Weed-free plots exhibited more tillers (5.76 plant-1) and accumulation (827.1 g m-2). The weed-free plots suppress weed by 75.4 %. In weed-free plots, nitrogen, phosphate and potassium consumption rose 19.4, 16.8 and 18.7 %, respectively. Application of oxyfluorfen (0.1 kg ha-1) fb 2,4-D (0.5 kg ha-1) resulted in highest net returns Rs. 88881 ha-1 with benefit-to-cost ratio (2.61). This 1 season study supports long-term experimentation, but it shows that 75 % RDN along with 25 % FYM and oxyfluorfen at 0.1 kg ha-1 (PE) followed by 2,4-D at 0.5 kg ha-1 (PoE) can boost finger millet productivity and profitability.